2020
DOI: 10.1002/jmri.27421
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Compressed Sensing Algorithms for Accelerating T Mapping of Human Brain

Abstract: Background 3D‐T1ρ mapping is useful to quantify various neurologic disorders, but data are currently time‐consuming to acquire. Purpose To compare the performance of five compressed sensing (CS) algorithms—spatiotemporal finite differences (STFD), exponential dictionary (EXP), 3D‐wavelet transform (WAV), low‐rank (LOW) and low‐rank plus sparse model with spatial finite differences (L + S SFD)—for 3D‐T1ρ mapping of the human brain with acceleration factors (AFs) of 2, 5, and 10. Study Type Retrospective. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The L + S reconstruction led to severe blurring at 16‐fold acceleration. This observation is in consistency with a recent work by Menon et al, 50 where a loss of fine features was also observed with L + S reconstruction for an acceleration rate of 10. The ghosting artifacts associated with L + S may be caused by insufficient suppression of the aliasing artifacts at high acceleration rates 16 .…”
Section: Discussionsupporting
confidence: 94%
“…The L + S reconstruction led to severe blurring at 16‐fold acceleration. This observation is in consistency with a recent work by Menon et al, 50 where a loss of fine features was also observed with L + S reconstruction for an acceleration rate of 10. The ghosting artifacts associated with L + S may be caused by insufficient suppression of the aliasing artifacts at high acceleration rates 16 .…”
Section: Discussionsupporting
confidence: 94%
“…The monotone fast iterative shrinkage algorithm with variable acceleration (MFISTA‐VA) 23 is used to minimize x . Although not tested here, other CS techniques such as using wavelets may be tested 24–27 …”
Section: Methodsmentioning
confidence: 99%
“…Although not tested here, other CS techniques such as using wavelets may be tested. [24][25][26][27]…”
Section: Reconstruction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review studies on qMRI reconstruction techniques are typically specific to a class of techniques such as compressed sensing, 3 MR fingerprinting [4][5][6] or deep-learning. 7,8 Alternatively, they are specific to a particular class of parameters of interest, such as relaxometry, 7,[9][10][11][12] or diffusion 13 parameters, or to a particular application domain, such as the knee, 14 or cardiac and abdominal imaging. 15 To facilitate the comparison among different reconstruction techniques used for accelerated qMRI, the current work presents a systematic review that provides a technical overview of the existing techniques, without confining to any specific parameter or application domain, and categorizes them based on methodology.…”
Section: Introductionmentioning
confidence: 99%